Phylogenetic composition of host plant communities drives plant‐herbivore food web structure. (2nd March 2017) - Volf, Martin; Pyszko, Petr; Abe, Tomokazu; Libra, Martin; Kotásková, Nela; Šigut, Martin; Kumar, Rajesh; Kaman, Ondřej; Butterill, Philip T.; Šipoš, Jan; Abe, Haruka; Fukushima, Hiroaki; et al.
Summary: Insects tend to feed on related hosts. The phylogenetic composition of host plant communities thus plays a prominent role in determining insect specialization, food web structure, and diversity. Previous studies showed a high preference of insect herbivores for congeneric and confamilial hosts suggesting that some levels of host plant relationships may play more prominent role that others. We aim to quantify the effects of host phylogeny on the structure of quantitative plant‐herbivore food webs. Further, we identify specific patterns in three insect guilds with different life histories and discuss the role of host plant phylogeny in maintaining their diversity. We studied herbivore assemblages in three temperate forests in Japan and the Czech Republic. Sampling from a canopy crane, a cherry picker and felled trees allowed a complete census of plant‐herbivore interactions within three 0·1 ha plots for leaf chewing larvae, miners, and gallers. We analyzed the effects of host phylogeny by comparing the observed food webs with randomized models of host selection. Larval leaf chewers exhibited high generality at all three sites, whereas gallers and miners were almost exclusively monophagous. Leaf chewer generality dropped rapidly when older host lineages (5–80 myr) were collated into a single lineage but only decreased slightly when the most closely related congeneric hosts were collated. This shows that leaf chewer generality has been maintained by feeding on confamilial hosts while only a few herbivores were shared between more distant plant lineages and, surprisingly, between some congeneric hosts. In contrast, miner and galler generality was maintained mainly by the terminal nodes of the host phylogeny and dropped immediately after collating congeneric hosts into single lineages. We show that not all levels of host plant phylogeny are equal in their effect on structuring plant‐herbivore food webs. In the case of generalist guilds, it is the phylogeny of deeper plant lineages that drives the food web structure whereas the terminal relationships play minor roles. In contrast, the specialization and abundance of monophagous guilds are affected mainly by the terminal parts of the plant phylogeny and do not generally reflect deeper host phylogeny. Abstract : Here the authors quantify the effects of host plant phylogeny on canopy insect communities, identifying the levels of host phylogeny playing the major role in the structure of their food webs. The authors show that the specific role of host plant diversity and phylogenetic composition differs among herbivore guilds depending on their specialization.